Fabrication and characterization of varistor-polymer composite based on zinc oxide - Fatehi, Asma (2012)
This research focuses on fabricating a varistor-polymer composite based on nanosized ZnO and micro-sized ZnO, and comparing their current-voltage characteristics. In addition, the influence of each dopant (Bi2O3, MnO, Co3O4) on the physical and electrical properties of varistor-polymer composite based on zinc oxide is investigated. Nano-sized varistor powder, micro-sized varistor powder and Bi2O3-MnO-Co3O4 doped ZnO micro powder were prepared via a combined solution and standard ceramic processing. Fabrication of a varistor-polymer nanocomposite and microcomposite was accomplished by the melt-blending technique. The characterization of varistor-polymer composites was carried out by X-ray diffraction data (XRD) analysis, Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM), Energy dispersive X-ray (EDAX), Thermal Gravimetry Analysis (TGA) and Fourier Transform Infra-red (FTIR) spectroscopy. The XRD pattern of nanocomposite revealed the high crystallinity of the composite compared to microcomposite. FTIR spectra confirmed physical interacting of polymer and varistor powder. TGA and DSC results revealed that temperature degradation and melting temperatures of nano composite were increased compared to micro composite. Manganese Oxide as one dopant of varistor powder stabilize thermal resistivity of the varistor-polymer composite compared to other metal oxides. The TEM image showed the spherical morphology of the nano-sized filler with the average size below 50 nm which were distributed homogeneously within the polymer. While, the SEM micrograph revealed the non uniform distribution of micro-sized fillers. FESEM and EDAX showed the presence of a bismuth-rich phase and a ZnO phase in the varistor powder. The current-voltage (I-V) characteristics suggested varistor-like behaviour when the concentration of nano-sized filler increased in contrast to micro-sized filler. Bismuth Oxide (as one dopant of varistor powder) has an important role in nonlinear properties of varistor-polymer composites.